2018
DOI: 10.1111/febs.14676
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the essential pathogenicity factor Rv1828, a MerR family transcription regulator from Mycobacterium tuberculosis

Abstract: The gene Rv1828 in Mycobacterium tuberculosis is shown to be essential for the pathogen and encodes for an uncharacterized protein. In this study, we have carried out biochemical and structural characterization of Rv1828 at the molecular level to understand its mechanism of action. The Rv1828 is annotated as helix‐turn‐helix (HTH)‐type MerR family transcription regulator based on its N‐terminal amino acid sequence similarity. The MerR family protein binds to a specific DNA sequence in the spacer region between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
3
3
0
Order By: Relevance
“…This, together with the strong conservation of our motif among many species, suggests that the motif proposed by us is more likely the correct one. Our results obtained for FtsR and Rv1828 together with the recently published characterization of Rv1828 [40] strongly support the notion that FtsR and its actinobacterial homologs are involved in transcriptional regulation of ftsZ . In line with this, the ftsZ promoter regions of various actinobacterial genera were found to contain DNA sequence motifs similar to the ones determined for FtsR and Rv1828 (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…This, together with the strong conservation of our motif among many species, suggests that the motif proposed by us is more likely the correct one. Our results obtained for FtsR and Rv1828 together with the recently published characterization of Rv1828 [40] strongly support the notion that FtsR and its actinobacterial homologs are involved in transcriptional regulation of ftsZ . In line with this, the ftsZ promoter regions of various actinobacterial genera were found to contain DNA sequence motifs similar to the ones determined for FtsR and Rv1828 (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Size-exclusion chromatography of affinity-purified FtsR-Strep (calculated mass 28.5 kDa) and comparison to standard proteins indicated that the protein forms a dimer (Additional file 1: Figure S11B). This is in line with the dimeric state of the homologous protein Rv1828 [40]. Purified FtsR-Strep was able to completely shift a 30-bp double-stranded oligonucleotide covering the predicted FtsR-binding site in the ftsZ promoter region at a 2-fold molar excess of the dimeric protein (Fig.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations